Seasonal variation of aerobic performance in soccer players according to positional role - Metaxas, T.; Sendelides, T.; Koutlianos, N.; Mandroukas, K. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The purpose of this study was to evaluate the seasonal variation in the cardiorespiratory fitness of soccer players according to positional role in the team. Methods: Thirty-two male soccer players U-19 years old were studied, consisting of 10 central defenders (18.2±0.9 years and 8.5±1.6 years of training (Group A), 12 midfielders (18±1 years and 8.1±1.4 years of training (Group B) and 10 attackers (18.2±0.9 years and 8.4±1.5 years of training (Group C). All subjects underwent anthropometric measurements and maximal exercise tests on a treadmill four times during their annual training cycle and maximal blood lactate accumulation analysis in order to verify that maximal exertion was reached. The measurements took place in the beginning and at the end of the preparation period, in the middle as well as at the end of the competitive season. Results: Group A showed increased V.O2max (mL.kg-1.min-1) by 19.3% in the 2nd measurement, by 22.9% in the 3rd and by 17.6% in the 4th compared to the beginning, respectively (P£0.05). The percentages of V.O2max (mL.kg-1.min-1) improvement were 19.5%, 22.1% and 17.7% for Group B and 24.6%, 27.2% and 21% for Group C, respectively (P<=0.05). No significant differences were observed between the three positional roles at any of the four times of the season. Conclusions: The results indicated that the maximal aerobic power of the players was not significantly different as regards their positional role in the team. The aerobic fitness as it was evaluated by the V.O2max and the exercise time to exhaustion, increased significantly after the training preparation period compared to the baseline values and remained relatively constant throughout the whole training season.